The vision of French Orientalism for the institutions of administration in the Abbasid era Book "Islam from its inception to the emergence of the Ottoman Empire by Claude Kahin a (Journal of the College of Basic Education, 2022)
This research revolves around the French Orientalist vision of the institutions of administration in the Abbasid era, the book of Islam from its inception until the emergence of the Ottoman Empire by Claude Kahin as a model Orientalism, and this is due to its great impact that it left in various ways, as well as a large group of prominent Orientalists whose writings have left an impact even on the rest of the schools of Orientalism, especially Claude Kahn. He delves into politics, culture and economics, and their implications. We saw how the educational institutions in the Ministry of Foreign Affairs and the conditions of these institutions, and his observations as a whole reflected the vision of the French Orientalist School of a part of the Islamic civilization and presented it at the height of the civilizational prosperity of Muslims and after their details were completed.